Upgrading TPQ Management Skills for TPQ Teachers in Grogol District, Sukoharjo - Suratno Suratno; Karimah Nur Azizah; Syahidah Asma Amanina; Sudarmadi Putra (I-Com: Indonesian Community Journal, 2024)
In the era of Industrial Revolution 4.0, religious knowledge is very necessary. This is because humans are spoiled by technological advances that are rational, practical, empirical and material in nature. TPQ is one of the non-formal institutions that can protect the Muslim generation from these dangers. However, in reality, many TPQs in Grogol District, Sukoharjo, are not managed well. The management structure, curriculum, and teaching methods are not well-regulated. Therefore, the STIM Surakarta Community Service Team held a seminar on managing TPQ with the aim of enabling TPQ teachers in the Grogol sub-district to manage TPQ well. This Community Service uses the Participatory Action Research (PAR) method. The stages followed are observation, problem identification, preparation, implementation, evaluation and publication. This community service activity succeeded in providing insight to TPQ teachers about good TPQ management.